1998
DOI: 10.1161/01.res.82.2.166
|View full text |Cite
|
Sign up to set email alerts
|

Possible Involvement of Stress-Activated Protein Kinase Signaling Pathway and Fas Receptor Expression in Prevention of Ischemia/Reperfusion-Induced Cardiomyocyte Apoptosis by Carvedilol

Abstract: Carvedilol, a new vasodilating beta-adrenoceptor antagonist and a potent antioxidant, produces a high degree of cardioprotection in a variety of experimental models of ischemic cardiac injury. Recent clinical studies in patients with heart failure have demonstrated that carvedilol reduces morbidity and mortality and inhibits cardiac remodeling. The present study was designed to explore whether the protective effects of carvedilol on the ischemic myocardium include inhibition of apoptosis of cardiomyocytes and,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
108
1
5

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 217 publications
(123 citation statements)
references
References 34 publications
9
108
1
5
Order By: Relevance
“…Apoptosis has been described in heart failure due to IDC and other cardiac diseases, 5 and beneficial effects of a long-term therapy with angiotensin-converting enzyme inhibitors as well as carvedilol, an antagonist at b-and a-adrenergic receptors, may involve the inhibition of cardiac apoptosis. [39][40][41] Up to now, the molecular pathways leading to the activation of the apoptotic signaling cascade, in particular, in the heart are not understood in detail. AP-2a has been shown to inhibit the activation of apoptosis mediated by the proto-oncogene c-myc, 42 and recently, AP-2a has been implicated in the antiapoptotic effects of the retinoblastoma gene product and in the induction of Bcl-2 in epithelial but not in NIH 3T3 mesenchymal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis has been described in heart failure due to IDC and other cardiac diseases, 5 and beneficial effects of a long-term therapy with angiotensin-converting enzyme inhibitors as well as carvedilol, an antagonist at b-and a-adrenergic receptors, may involve the inhibition of cardiac apoptosis. [39][40][41] Up to now, the molecular pathways leading to the activation of the apoptotic signaling cascade, in particular, in the heart are not understood in detail. AP-2a has been shown to inhibit the activation of apoptosis mediated by the proto-oncogene c-myc, 42 and recently, AP-2a has been implicated in the antiapoptotic effects of the retinoblastoma gene product and in the induction of Bcl-2 in epithelial but not in NIH 3T3 mesenchymal cells.…”
Section: Discussionmentioning
confidence: 99%
“…The current study supports an antiapoptotic role for carvedilol in focal ischemia as evidenced by fewer TUNEL positive cells in the treated groups compared with controls ( Fig 3). There is also evidence that carvedilol prevents apoptosis in congestive heart failure (Yue et al, 1998). It should be noted that a TUNEL-positive reaction can occur in cells undergoing necrosis (Rink et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Carvedilol's antiapoptotic effects may be related to its antioxidant properties. However, Yue et al (1998Yue et al ( , 1999 have shown that carvedilol may inhibit ischemia-induced myocardial apoptosis by downregulating the stress-activated protein kinase (SAPK) pathway and the expression of the Fas receptor.…”
Section: Discussionmentioning
confidence: 99%
“…The hearts were "freeze-clamped" by using precooled aluminum tongs and pulverized under LN 2 . 20 The powder was resuspended in ice-cold lysis buffer, and the protein content in the detergent-soluble supernatant fraction was measured as described previously. 7 SAPK, p38 MAPK, and MAPKAP K2 kinases were immunoprecipitated with antibodies specific for JNK1 and JNK2 (Santa Cruz), p38 MAPK (SmithKline Beecham), or MAPKAP K2 (Dr J. Landry, University of Quebec, Montreal) and assayed by using glutathione-S-transferase-c-Jun , glutathione-S-transferase-activating transcription factor-2, or heat shock protein 27 as the substrate, respectively, as described in our previous studies.…”
Section: Sapk P38 Mapk and Mapk-activated Protenine Kinase 2 (Mapkamentioning
confidence: 99%